FROM CLASSROOM TO CAREER: STUDENT PERCEPTIONS OF WORKPLACE SIMULATION IN IT EDUCATION (Proceedings of the International Conference on Education, 2025)
Project-based learning (PBL), a methodology used in experiential learning, is a common approach to sustainable education intended to deliver quality education. PBL is a student-centred pedagogical approach that has shown effectiveness in addressing challenges found in traditional teacher-centric environments. In IT, students are often engaged with real-world problems that require a diverse set of competencies beyond foundational knowledge. Due to this reason, PBL has been practised in IT education mainly through final-year capstone projects. These capstone courses are based on projects that offer valuable real-world experience but often lack sufficient time for students to fully solidify their knowledge and skills. This is because these courses are typically offered in the final year of the degree programme. To overcome this challenge, we use a series of courses called “Studio” that immerse students in a simulated work environment from their first year. These courses gradually introduce students to real-world practices and technologies, allowing sufficient time to consolidate their learning. This study aimed to investigate the experiences and perceptions of the students towards this model. A semi-structured online survey was used to collect data from students enrolled in Studio courses. The sample consists of forty-five students enrolled as international students in the BIT programme. Descriptive and exploratory data analysis techniques were primarily applied to analyse their feedback while open-ended questions were examined to identify the emerging themes related to the student experience. While this study is still a work in progress students generally view the Studio courses positively and value the skills they have gained over time. Feedback highlights the importance of providing time for knowledge consolidation and shows that students appreciate the gradual exposure to technical topics. Integration of soft and technical skills over time seemed to have increased students’ confidence in managing real-world projects.
Keywords: workplace simulation; project-based learning; IT undergraduates; IT curricula; scaffolded learning